Curious George. A day at the library - Rey, Margret; Rey, H. A. (Hans Augusto), 1898-1977.; Welker, Frank; Universal Studios Home Entertainment (Firm); PBS for Kids. ([United States] : Universal, 2011)
What's George's favorite place to go for adventure? The library! George loves to read, because in books you can be a pirate, a spaceman, even a robot! Or learn about photography, strange animals and how to make it snow. What better place for the world's most curious monkey?
1. Book monkey 2. George's super subway adventure ; 3. Monkey size me ; 4. Whistlepig Wednesday ; 5. Signs up ; 6. Snow use ; 7. The big picture; 8. Sees the light.
Title from disc surface.
Widescreen.
DVD, Dolby Digital 2.0 stereo.
Closed captioned.
Keywords: Curious George (Fictitious character) -- Juvenile films; Libraries -- Juvenile films; Curiosity -- Juvenile films; Bicycles -- Juvenile films; Animated television programs; Children's television programs; Television programs for the hearing impaired